COMPARISON BETWEEN AMMI, W-AMMI AND GGE METHODOLOGY IN THE CONTEXT OF SIMULATED DATA - SARTI, Danilo Augusto; DIAS, Carlos Tadeu dos Santos (Brazilian Journal of Biometrics, 2020)
Genotype x environment interaction is a key issue in plant breeding and new cultivars development. The modelling of such interactions has huge importance to decisions in plant breeding and breeding program optimization. In this context AMMI, W-AMMI and GGE models claims to address such interactions. The present paper aims to check the behaviour of such models in face of data with well behaved parametric properties. The results shows that the three models are efficient to model GxE interactions.